Pengetahuan Tentang Gangguan Jiwa dengan Kemampuan Keluarga Merawat Orang dengan Gangguan Jiwa - Vrigia Lumeohe; Helly Katuuk; Sri Wahyuni (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
People with mental illness are people who have physical, mental, social, growth, development, and quality of life problems. Family can be a key factor in healing. Families must have cognitive, affective and psychomotor abilities. The purpose of the study was to find out the correlation between knowledge about mental disorders with the ability of families to care for people with mental disorders at the Poigar Health Center, Poigar District. The study used descriptive analytic method with cross sectional approach. The sample was 33 respondents with non probability sampling, total sampling technique. Data collection was carried out by distributing questionnaires. The data that has been collected was then processed by running the SPSS computer program version 25.0 to be analyzed with the chi square statistical test with a significance level (α) of 0.05. The results of the study with the chi square test showed a p-value of 0.000 with a significant level <0.05. The p-value (0.000) is smaller than α (0.05) so that H0 is rejected and Ha is accepted. The conclusion is that there is a significant correlation between knowledge about mental disorders with the ability of families to care for people with mental disorders.